Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Menulis Teks Eksplanasi pada Siswa Kelas XI Sekolah Menengah Atas Al Washliyah 1 Medan Tahun Ajaran 2025–2026 - Fatmawati, Dara; Deliani, Susy; Ray, Sukma Adelina (Universitas Islam Sumatera Utara, 2025)
Education in Indonesia is currently guided by an independent curriculum that emphasizes freedom of expression and creativity in learning. However, in Indonesian language instruction—particularly in explanatory text materials—students still demonstrate limited writing proficiency and difficulty articulating ideas coherently. The persistence of teacher-centered methods, such as lecturing, has contributed to this issue. Therefore, this study aims to examine the effect of the guided inquiry learning model on students’ ability to write explanatory texts in grade XI at Al Washliyah 1 High School, Medan, during the 2025–2026 academic year. Employing a quantitative experimental design, specifically a one-group pre-test and post-test model, data were collected from a sample of 23 students selected through random sampling from a population of 52. The study was conducted from July 25 to 29, 2025. Hypothesis testing using the t-test revealed a mean score of 81.35 in the experimental class and 79.43 in the control class, with a t-value of 15.38, exceeding the critical value of 2.074. These findings indicate that the guided inquiry learning model significantly enhances students’ ability to write explanatory texts.